Green tea extract and nanocellulose embedded into polylactic acid film: Properties and efficiency on retarding the lipid oxidation of a model fatty food. (March 2021) - Vilarinho, F.; Stanzione, M.; Buonocore, G.G.; Barbosa-Pereira, L.; Sendón, R.; Vaz, M.F.; Sanches Silva, A.
Graphical abstract: Highlights: PLA/CNC and PLA/CNC/GTE films prepared by direct melt processing. PLA/2%CNC/1%GTE nanocomposite film, showed good dispersion level of CNC and GTE. PLA/2%CNC/1%GTE nanocomposite film presents an efficient barrier effect. PLA/2%CNC/1%GTE nanocomposite film presents a good macroscopic mechanical behavior. The active films effectiveness on retarding lipid oxidation was evaluated in a model food. Abstract: Eco-friendly and antioxidant bioactive films based on polylactic acid (PLA), loaded with cellulose nanocrystals (CNC) and green tea extract (GTE) were prepared by direct melt processing. GTE was chemically characterized by using high performance liquid chromatography (HPLC), coupled with tandem mass spectrometry. The antioxidant, physical, thermal, mechanical and microstructural properties of the produced films were investigated. The efficiency of the active films on retarding the lipid oxidation of the salami, was evaluated by the thiobarbituric acid reactive substances (TBARS) and p -anisidine value. Experimental results highlight that the PLA/2%CNC/1%GTE nanocomposite film (film containing 2 wt% of CNC and 1 wt% of GTE) shows the highest reduction in terms of oxygen transmission ratio and water vapor permeability (60 % and 33 % respectively) and the optimal macroscopic mechanical behavior. However, it shows a slight antioxidant activity only at short storage time, namely 7 and 15 days. Overall, PLA/2CNC nanocomposite film exhibits the best compromise in terms of improvement of material properties and of effectiveness in retarding lipid oxidation at short and long storage time, mainly related to its enhanced barrier properties.